QIS ANALISIS QUALITY INFORMATION SYSTEM (QIS) MENGGUNAKAN MODEL ISO 9126 PADA SIAKAD - Moh. Ali Fikri; Riyan Farismana; Dita Rizki Amalia (Politeknik Negeri Indramayu, 2022)
Measuring the quality of an information system can be assessed through certain measures and methods. The method that can be used is ISO 9126, where this method can define the quality of information systems in order to get an evaluation of a system that is running. There are six system quality variables that use ISO 9126, namely functionality, reliability, usability, efficiency, maintainability, and portability. Based on the ISO 9126 standard, the results of the Quality Information System (QIS) analysis using the ISO 9126 Model on SIAKAD obtained a functionality value of 20.16% and then usability of 20.01%, probability of 15.99%, maintainability of 15.95%, efficiency of 15.90% and the smallest reliability efficiency is 11.99%. Thus the quality of the SIAKAD information system is very good at the Functionality level and not very good at the Efficiency level. Based on Figure 5, it states that Quality System Information (QIS) has a score of 75.80%. Thus, through the analysis of the QIS category at SIAKAD Indramayu State Polytechnic, namely Good. Meanwhile, 24.20% according to respondents said it was not good